2009
DOI: 10.1108/09593840910962212
|View full text |Cite
|
Sign up to set email alerts
|

IT occupational culture: the cultural fit and commitment of new information technologists

Abstract: PurposeAs the shortage in the information technology (IT) workforce continues, it is becoming increasingly important to understand the cultural dimensions of IT occupations that attract or drive away potential IT professionals. In the present study, the authors take an occupational culture approach to study the cultural fit of newcomers to IT occupations and to understand how young people perceive the culture embedded in this occupational community as they become part of it.Design/methodology/approachThe autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 51 publications
0
53
0
Order By: Relevance
“…Professional bodies have sought to credentialise skills in IT, but the speed of change in IT has prevented them achieving occupational closure (Danner, 1998). One strand of studies of IT has applied Trice's (1993) theoretical framework to IT professionals (Guzman and Stanton, 2009;Guzman et al, 2008;Ramachandran and Rao, 2006). These studies have found that IT professionals have a distinctive occupational sub-culture.…”
Section: It Services and It Professionals In Hementioning
confidence: 99%
“…Professional bodies have sought to credentialise skills in IT, but the speed of change in IT has prevented them achieving occupational closure (Danner, 1998). One strand of studies of IT has applied Trice's (1993) theoretical framework to IT professionals (Guzman and Stanton, 2009;Guzman et al, 2008;Ramachandran and Rao, 2006). These studies have found that IT professionals have a distinctive occupational sub-culture.…”
Section: It Services and It Professionals In Hementioning
confidence: 99%
“…From an organizational perspective, Schein [5] argued strongly that cultural studies must use qualitative methods in order to tap and understand deep structure issues. Unfortunately, within the IS discipline, Leidner and Kayworth [9] found that there is a predominance of survey designs and positivist case studies in IS culture research, with very few ethnographies or other interpretive designs.…”
Section: Surveys Versus Ethnographymentioning
confidence: 99%
“…One of the social and leadership factors often mentioned as a contributor to information sabotage behavior is the culture/environment (Appelbaum, Iaconi, & Matousek, 2006;Appelbaum, Shapiro, & Molson, 2007;Guzman & Stanton, 2009;Hunker & Probst, 2011;Leidner & Kayworth, 2006;Warkentin & Willison, 2009). Research on the context of the possible different organization cultures that enable information sabotage acts to occur has been relatively neglected except for the above mentioned data leakage and hacking literature (Guzman & Stanton, 2009;Leidner & Kayworth, 2006).…”
Section: Organizational Culture Introductionmentioning
confidence: 99%
“…Research on the context of the possible different organization cultures that enable information sabotage acts to occur has been relatively neglected except for the above mentioned data leakage and hacking literature (Guzman & Stanton, 2009;Leidner & Kayworth, 2006). Organizational culture research may also lend answers to a fundamental question as to why managers could be tolerant or intolerant of such acts (Huth et al, 2013;Richards, 2008;Warkentin & Willison, 2009).…”
Section: Organizational Culture Introductionmentioning
confidence: 99%